Cybersecurity Awareness In HR: Protecting Employee Data in the Digital Era - Maulidar, Maulidar; Wanda, Edi; Hijriatin, Maudi (Malikussaleh University, Aceh, Indonesia, 2025)
Cybersecurity in team member data management is critical to corporate operations, especially in the e-commerce industry, which faces continuously evolving digital threats. This study evaluates cybersecurity awareness in Tokopedia's Human Resources (HR) department and the effectiveness of security policies implemented following the 2020 data breach incident. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis. The findings indicate that while Tokopedia has strengthened its data security policies, significant challenges remain in team member compliance with security protocols, policy implementation complexity, and limited understanding of cyber threats. To address these challenges, this study recommends an approach based on interactive training programs, adopting Zero Trust Architecture (ZTA) and using Artificial Intelligence (AI) for cybersecurity threat detection. Furthermore, strengthening cybersecurity culture through management involvement and team member incentive systems is also identified as a strategic measure to enhance awareness and compliance with security policies. With proper implementation, Tokopedia can enhance team member data protection, reduce cybersecurity risks, and ensure long-term information security sustainability within the company.